Development, validation and application to real samples of a multiresidue LC‐MS/MS method for determination of β2‐agonists and anabolic steroids in bovine hair†. (10th September 2014) - Leporati, M.; Bergoglio, M.; Capra, P.; Bozzetta, E.; Abete, M. C.; Vincenti, M.; Giorgi, Gianluca
<x xml:space="preserve">Abstract</x> β2‐agonists are often abused in cattle breeding because of their effects on animal growth and meat properties. The use of β2‐agonists as growth promoters is forbidden in the European Union (Council Directive 96/23/EC classifies them into group A of Annex I), due to their toxicity and carcinogenic properties, as for anabolic steroids, which are often administered in combination with β2‐agonists, to promote the storage of proteins and increase muscle size. A unique confirmatory liquid chromatography–tandem mass spectrometry (LC‐MS/MS) method for the quantitative detection of 13 β2‐agonists and anabolic steroids plus the qualitative identification of other three analytes in bovine hair was developed and validated, according to Decision 2002/657/CE. Hair samples were washed with dichloromethane, digested within a NaOH solution and subjected to liquid–liquid extraction. The analysis was performed by high performance liquid chromatography coupled to a triple quadrupole mass spectrometer operating in the selected reaction monitoring mode. The absence of matrix interferents, together with good repeatability of both retention times and relative abundances of diagnostic transitions, allowed the correct identification of all analytes. The quantitative calibrations obtained from spiked blank hair samples proved linear in the range tested. CCα and CCβ ranged from 0.5 ng/g to 30 ng/g. Intralaboratory reproducibility (CV%) ranged between 5.0 and 17.7 and trueness between 96% ± 7% and 105% ± 8%. The applicability of the method to real positive samples was demonstrated for both β2‐agonists and anabolic steroids. 17α‐boldenone was found in most (70%) hair samples obtained from untreated animals, supporting the hypothesis of endogenous production of this steroid. Copyright © 2014 John Wiley & Sons, Ltd.